Social anxiety disorder: relevance and perspectives - Avramchuk, Oleksandr (Psychosomatic Medicine and General Practice, 2019)
Background. Epidemiological studies indicate that social anxiety disorder as one of the most common mental health disorders. However, many patients do not seek or receive help, despite the prevalence of social anxiety disorder, the large amount of information, the possibilities of psychotherapy and medical treatment. Aim. Generalization of actual knowledge and research on the aetiology and pathogenetic mechanisms of social phobias and coverage of the actual issues of low referral of people suffering from social phobia. Methods. For review, the following databases, such as ScienceDirect, ResearchGate, PubMed and Google Scholar, were used. The search was performed using the keywords: social anxiety disorder, sociophobia, social anxiety, cognitive-behavioral model, neurobiology, mental health. Results. The general information about social anxiety disorder, its prevalence and its consequences were covered. The main etiological mechanisms, modern views on the neurobiological and psychological basis of the disorder are considered. In addition, the peculiarities of the clinical picture and its influence on the social functioning of the individual, including the referral of help, were analyzed. The aspects that are useful to consider during the development of recommendations for specialists in general medical practice and centers of public mental health were suggested. Conclusions. A social anxiety disorder should be considered as a complex mental health disorder. Recognition of signs of social anxiety disorder in their component often leads to a false interpretation of clinical signs as manifestations of depression or other neurotic disorders among primary care professionals. Informing general practitioners and specialists of public mental health centers about the traits of the clinical picture and the social functioning of patients with this disorder can help to overcome the stigma and improve the referral of qualified assistance.